Sustainable Governance and Financial Strategies: Empirical Studies on Business, Public Sector, and Enviromental Management - Sundari, Jualian; Prasetio, Januar Eko; Kusharyanti, Kusharyanti; Nilmawati, Nilmawati; Ridzal, Nining Asniar; Nirwana, Nirwana; Nurmalasari, Putri; Maryanti, Siti Nur; Hastuti, Sri; Suryaningsum, Sri; Sutoyo, Sutoyo; Rasyid, Syarifuddin; Winata, Widya; Zuhrotun, Zuhrotun (AIBPM Publisher, 2026)
Sustainable Governance and Financial Strategies: Empirical Studies on Business, Public Sector, and Environmental Management presents a timely and insightful collection of studies addressing critical issues at the intersection of governance, finance, and sustainability. The diversity of contributors and topics highlights the dynamic challenges faced by organizations across sectors in an era marked by rapid environmental, economic, and regulatory shifts.This book successfully bridges academic theory and practical implementation, offering valuable perspectives for scholars, policymakers, and practitioners alike. It explores how financial strategies and sustainable governance models can be effectively applied to enhance institutional performance, accountability, and environmental stewardship.As someone who has observed the evolving landscape of financial governance and sustainability practices, I find this volume to be a vital contribution that not only informs but also inspires future research and collaboration.